PERANCANGAN PLTMH SUNGAI YEH HA DI KARANGASEM DENGAN TURBIN CROSSFLOW - Virgunia, D. A.; Sukerayasa, I W.; Ariastina, W. G.; Setiawan, I N.; Giriantari, I. A. D.; Satya Kumara, I N.; Satya Kumara, I N. (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUM, 2024)
Yeh Ha River in Ababi Village, Karangasem Regency, Bali, is a river that originates from the Yeh Ha springs and is used as a bathing place. This river has the potential for a new renewable energy source that can be utilized for the Micro Hydro Power Plant (MHPP). Discharge measurements were carried out for a week on one of the Yeh Ha spring source channels during the dry season. The results showed an average discharge of 0.201 m3/s. The discharge data used is the minimum potential energy that can be absorbed. Based on the measured discharge data and the used head of 4.6 m, the Tanaka Suiryoku Turbine Selection Chart shows that the crossflow turbine meets the turbine selection criteria. The results of the analysis and calculations show that the available power at the turbine is 8 kW with an efficiency of 80%. A 3-phase synchronous generator with a permanent magnet rotor was selected based on a comparison of the types, specifications, and characteristics of the generator to match the turbine capacity. The output power generated by the generator is 6 kW with a rotational speed of 1500 rpm and a generator efficiency of 90%.